Why the Polarizing of Addiction Professionals Regarding Abstinence versus Harm Reduction Therapy is so Absurd - Scott W Stern (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
During the past 20 years I've been in practice, I have found that all addiction treatments are, in fact, some form of harm reduction. We've yet to find an infallible treatment for addictions and substance use disorders. However, the change in the DSM terminology is very significant. It differentiates diagnoses of substance abuse and chemical dependency from its evolved diagnosis of substance use disorder - mild, moderate or severe. Those with severe diagnoses (co-morbidity involving diabetes, liver damage, severe psychiatric conditions, dementia, legal, etc) would certainly be appropriate candidates for abstinence over moderation. But as I see it, at the end of the day, from moderation to abstinence it's all harm reduction. For every patient who repeatedly relapses and is referred to the "higher level of care," this, too, is about harm reduction. We've learned how poor the success rates are at inpatient facilities that practice abstinence-only 12 step model approaches. Without guarantee of outcomes, this too is a harm reduction approach. In this regard, I believe the term "harm reduction" is obsolete. It is a "given" in any treatment to practice some form of harm reduction. The professional who believes relapse prevention techniques and behavior modification are not a form of harm reduction is terribly misinformed.